ANALISIS PENOLAKAN PERMOHONAN UJI MATERIIL PERATURAN KOMISI PEMBERANTASAN KORUPSI NOMOR 1 TAHUN 2021 - Gilang Narawangsa Namara; Adiasih, Ning; Narawangsa Namara, Gilang (Reformasi Hukum Trisakti, 2023)
The Supreme Court's existence is inextricably linked to its status as the highest court in the land, with the power to physically examine and assess legal rules to determine whether a product is legal in terms of content (material) that is incompatible with a higher or higher level. The issue is how the judge's considerations in the Supreme Court decision No. 26/P/HUM/2021 in light of Law No. 19 of 2019 concerning the Second Amendment to Law No. 30 of 2002 regarding the Corruption Eradication Commission (KPK) and its decision Constitutional Court Number 70/PUU-XVII/2019 and the authority of the KPK after the issuance of Supreme Court Decision Number 26/P/HUM/2021 on the Eradication of Corrupt Practices in Indonesia. The research is normative, using secondary data, analyzed qualitatively, deductive conclusions. The results of the research and discussion are that the plaintiff's request must be accepted by the panel of judges who tried the case without changing the permit. The author has opinion that the Supreme Court decision is inconsistent with the applicable laws and regulations. Conclusion: there are differences in interpretation and meaning regarding the national vision test and there is no change in authority before and after decision 26/P/HUM/2021 which is attached to the national vision test of Law No. 19 of 2019.